Development of inferential Models: Prediction of Research Octane Number in Catalytic Reforming Units - Dias, Tiago Alexandre Garcia (2021)
Doctoral Thesis in Refining, Petrochemical and Chemical Engineering, presented to the Department of Chemical Engineering, Faculty od Sciences and Technology of the University of Coimbra.